2017
DOI: 10.1136/bmjspcare-2017-001354
|View full text |Cite
|
Sign up to set email alerts
|

Integrating palliative care into neurology services: what do the professionals say?

Abstract: ObjectivesEvaluations of new services for palliative care in non-cancer conditions are few. OPTCARE Neuro is a multicentre trial evaluating the effectiveness of short-term integrated palliative care (SIPC) for progressive long-term neurological conditions. Here, we present survey results describing the current levels of collaboration between neurology and palliative care services and exploring the views of professionals towards the new SIPC service.MethodsNeurology and palliative care teams from six UK trial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…It is patient-centered and involves diagnosis of clinical problems at all stages, rehabilitation to maintain function, care coordination and appropriate palliation to relieve symptoms". Recently, an increasing number of authors have focused on the integration of palliative care into neurology [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It is patient-centered and involves diagnosis of clinical problems at all stages, rehabilitation to maintain function, care coordination and appropriate palliation to relieve symptoms". Recently, an increasing number of authors have focused on the integration of palliative care into neurology [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary palliative care practice and research focuses on disease-oriented (cancer and noncancer disease) [42,43] and setting-oriented (palliative ward, ED, intensive care unit, home-based, long-term care facility, and community-based setting) approaches. [44][45][46][47] Triage level I resuscitation is a common pathway of patients with advanced and progressive deterioration illnesses, as well as those with incurable frailty or co-existing conditions. Our study showed the average number of survival days of post-ED triage level I resuscitation is 351 days, which fits the definition of palliative care in the time dimension.…”
Section: Results Discussionmentioning
confidence: 99%
“…Our training course has helped the HPs (i) develop a new concept of PC centred on the response to the needs of people [43] and not only to care; (ii) understand that PC can also be extended to non-oncological patients [44,45] in advanced illness stages; (iii) gain empowerment and increased selfesteem from learning about the logistical and structural organization of PC to activate and implement PC [46][47][48]; (iv) appreciate the need to share personal aspects of their professional life; (v) appreciate the cooperation and joint multiple competences that enable a synergistic approach and enhanced outcomes [7,49].…”
Section: Discussionmentioning
confidence: 99%
“…The training programme, lasting 4 hours in two different editions to facilitate participation, was taught by II-level PC specialists to health professionals of all departments (I-level). The training focussed on the vision of PC by the World Health Organization (WHO) [1], the purpose of a PC unit in hospital and the sharing of PC needs in hospital wards [7,34].…”
Section: The Interventionmentioning
confidence: 99%